Integration of forest policy goals at European, national and sub-national levels. The case of fire prevention and biomass production - Ferranti, Francesca (Natural Resources Institute Finland, Luke, 2016)
Forest fire prevention and production of forest biomass for energy are receiving increasing attention in forest policy and governance. At European Union level, legislations and policies were formulated to regulate the way Member States deal with these two topics. Consequently, actions have been taken by Member States as well as lower policy levels to implement European requirements. This study analyzed the extent to which forest fire prevention and the production of forest biomass for energy were integrated in European Union, national and regional contexts. Spain and Catalonia (one of the Spanish Autonomous Communities) were chosen as case studies. The study focused mainly on integration in policy formulation but it provided insights also on aspects related to policy implementation. Results showed that while at European level the two topics were weakly connected in policy formulation, at lower policy levels the strength of this integration increased. Nevertheless, local stakeholders mentioned the need to improve this integration at regional policy level. In the implementation context, forest fire prevention and biomass production were better integrated than in the formulation context, thanks to initiatives taken by actors who played a key role in the Catalan arena.
Poster
Keywords: European Union; Spain; Catalonia; literature review; stakeholders; questionnaire